Fully Printed Flexible Crossbar Memory Devices with Tip‐Enhanced Micro/Nanostructures. (4th April 2019) - Pan, Qi; Su, Meng; Zhang, Zeying; Cai, Zheren; Li, Yifan; Huang, Zhandong; Qian, Xin; Hu, Xiaotian; Li, Fengyu; Dong, Huanli; Song, Yanlin
Abstract: Flexible memory devices with optimal tip‐enhanced structures and high density are necessary for data storage devices. Printed electronics combine an efficient manufacturing approach with diverse materials adoptability and multidimensional patterns. However, the precision of the printed structures and the nonuniform of the interfaces restrict the storage density and performance severely. A full printing strategy to fabricate crossbar memory devices with triangular prism–structured Ag microwire electrodes and Ag/silk fibroin conformal interlayers is reported. Based on tip‐enhanced microelectrodes and flexible function layers, these crossbar memory devices show a high I ON / I OFF ratio (10 6 at 1 V) and sufficient retention time (>10 4 s) under 5 mm curvature radius bending. Devices with 2.5 × 10 5 bits cm −2 storage density can be printed (10 3 higher than previously reported results), which enables efficient implement of pattern matching in visual display. This full printing strategy offers efficient fabrication for highly integrated flexible memories and 3D multilayer microdevices. Abstract : A full printing strategy is proposed for fabricating flexible crossbar memory devices with tip‐enhanced structures and uniform interfaces. The memory devices achieve a high density of 2.5 × 10 5 bits cm ‐2 and high ON/OFF ratio (≈10 6 ) under bending condition and can be applied in a visual display. This strategy accelerates the fabrication of multi‐layer, even 3D, crossbar microelectronic systems.